Political linguistic personality of the statesman S. Seifullin: discursive characteristics (Eurasian Journal of Philology Science and Education, 2024)
The article defines all the linguistic means denoting political vocabulary. Linguistic concepts such as“political communication”, “political discourse” are considered, a number of linguistic units that expressthem are defined. It is established that language and politics are not considered separately from eachother, the analysis of the political system in Kazakhstan of various nature using the language, positions,statements of public and state figures, political leaders should be carried out at the junction of political,philological and linguistic research.A number of basic terms and methods covering the main problems of political linguistics are defined,and an explanation is given to each. In Kazakh society the place in the political discourse of Alash leadersand figure S. Seifullin, recognized on the basis of his works as political leaders, statesmen, conductingpolitical discussions of democratic-enlightenment, enlightenment-revolutionary orientation is characterized. So far, the language of political leaders has not been studied. Cognitively studied only on the basisof their works. Furthermore, the political linguistic image of S. Seifullin, who was recognized as a socialfigure, has been identified through the articles published in newspapers. In order to analyze the languageof the statesman, the periods of S. Seifullin’s active service to the nation and state were taken as a basis,and the use of mottos has been defined.The relevance of our research lies in the study of the political linguistic personality of public figureswho lived in Kazakh society within the framework of political discourse, the formation of a political linguistic personality based on slogans, reports, journalistic articles of socio-political content using stylisticstructures and types of tropes of artistic and political image in the language.The practical significance of the conclusions formulated in the article is relevant for linguists, Alashscholars, literary critics and other readers.Key words: politics, language, political linguistics, political lexis, political discourse, linguistic personality.